2016
DOI: 10.1097/md.0000000000004498
|View full text |Cite
|
Sign up to set email alerts
|

Effect of perioperative crystalloid or colloid fluid therapy on hemorrhage, coagulation competence, and outcome

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 55 publications
(133 reference statements)
4
36
0
2
Order By: Relevance
“…This and the potential impairment of renal function provide the reason for dose limitation (30 ml/kg). A recently published metaanalysis showed that HES application can result in a larger intraoperative blood loss compared to crystalloid therapy alone [66]. However, it must be noted that larger blood losses are often not appropriately treated by the sole application of crystalloid.…”
Section: Do These Considerations Also Apply To the Use Of Hes Preparamentioning
confidence: 99%
“…This and the potential impairment of renal function provide the reason for dose limitation (30 ml/kg). A recently published metaanalysis showed that HES application can result in a larger intraoperative blood loss compared to crystalloid therapy alone [66]. However, it must be noted that larger blood losses are often not appropriately treated by the sole application of crystalloid.…”
Section: Do These Considerations Also Apply To the Use Of Hes Preparamentioning
confidence: 99%
“…However, synthetic colloid administration is associated with coagulopathy and increases the need for red blood cells transfusion, as was consistently shown in large RCTs that compared crystalloids to HES in sepsis and critically ill patients 2 4 . Increased risk of bleeding after HES administration was also found in meta-analyses of RCTs in cardiac surgery patients and in the perioperative period 23 , 24 . Furthermore, there is strong evidence for prolonged bleeding times and decrease in clot firmness from in-vitro studies 25 and evidence of increased bleeding and mortality in animal studies 26 28 .…”
Section: Discussionmentioning
confidence: 63%
“…Additionally, our results are in accordance with a metaanalysis published by Rasmussen. 37 Patients in group RA-HES received significantly more crystalloids than patients in group RA (Table 3). This can be explained by the increased blood loss experienced by patients in group RA-HES, which was not fully compensated by the administration of HES and PRBC.…”
Section: Discussionmentioning
confidence: 98%